2015
DOI: 10.1111/hiv.12300
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk prediction in HIV‐infected patients: comparing the Framingham, atherosclerotic cardiovascular disease risk score (ASCVD), Systematic Coronary Risk Evaluation for the Netherlands (SCORENL) and Data Collection on Adverse Events of Anti‐HIV Drugs (D:A:D) risk prediction models

Abstract: When using FHS-CVD and FHS-CHD, a higher overall CVD risk was attributed to the HIV-infected patients than when using the D:A:D, ASCVD and SCORE-NL models. This could have consequences regarding overtreatment, drug-related adverse events and drug-drug interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 42 publications
1
44
1
4
Order By: Relevance
“…Prior studies have also suggested that the FRS overestimates CVD risk among individuals with HIV [34], however other studies have raised concerns about underestimation of CVD risk among individuals with HIV using the FRS as well [11]. In our cohort, the FRS and ASCVD Risk Scores both identified age and smoking as correlates of 10-year CVD risk ≥10%, which is not surprising given they are factored into the risk models themselves.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Prior studies have also suggested that the FRS overestimates CVD risk among individuals with HIV [34], however other studies have raised concerns about underestimation of CVD risk among individuals with HIV using the FRS as well [11]. In our cohort, the FRS and ASCVD Risk Scores both identified age and smoking as correlates of 10-year CVD risk ≥10%, which is not surprising given they are factored into the risk models themselves.…”
Section: Discussionsupporting
confidence: 46%
“…For individuals ≥20 years of age, the FRS calculates 10-year predicted risk of CVD based upon a model comprised of age, sex, TC, HDL-c, SBP, current treatment for hypertension and cigarette smoking (anytime in the past month) [18]. The CVD risk prediction model also categorizes individuals as low (<10% 10-year risk), intermediate (10–20% risk) or high risk (≥20% risk) for coronary heart disease [3, 19, 20]. …”
Section: Methodsmentioning
confidence: 99%
“…We found concordance in the proportion of individuals classified as high risk by each of the CVD prediction equations we evaluated but exceeded the proportion of HIV-infected patients classified in the highest CVD risk stratum in other reports [36, 37]. Other studies have reported moderate or low concordance in CVD risk score stratification among risk prediction equations [3638].…”
Section: Discussioncontrasting
confidence: 45%
“…Other studies have reported moderate or low concordance in CVD risk score stratification among risk prediction equations [3638]. The HOPS cohort had a higher prevalence of overweight or obese participants than that reported in other HIV-infected populations to which the risk prediction equations have been applied [18, 19, 37, 38]. The HOPS cohort may have differed from these other populations in additional important ways, including by sociodemographic and insurance status, or healthcare-seeking behaviors that we could not assess.…”
Section: Discussionmentioning
confidence: 99%
“…Un altro studio cross-sectional olandese ha arruolato 997 pazienti con infezione da HIV e valutato il loro rischio cardiovascolare utilizzando gli algoritmi Framingham, ACC-AHA, D:A:D e un modello nazionale per il calcolo del rischio di malattia coronarica. In questo studio l'equazione di Framingham tendeva a sovrastimare il rischio coronarico nei pazienti HIV-positivi rispetto agli altri modelli, che apparivano più accurati (15). Uno studio italiano di coorte ha confrontato i modelli di Framingham, ACC-AHA e D:A:D in 2550 pazienti HIV-positivi con un follow-up di 17337 pazienti-anno.…”
Section: Valutazione Del Rischio Cardiovascolareunclassified